Paroxysmal Genetic Movement Disorders and Epilepsy - de Gusmão, Claudio M.; Garcia, Lucas; Mikati, Mohamad A.; Su, Samantha; Silveira-Moriyama, Laura (Frontiers in Neurology, 2021)
Abstract : Paroxysmal movement disorders include paroxysmal kinesigenic dyskinesia, paroxysmal non-kinesigenic dyskinesia, paroxysmal exercise-induced dyskinesia and episodic ataxias. In recent years, there has been renewed interest and recognition of these disorders and their intersection with epilepsy, at the molecular and pathophysiological levels. In this review, we discuss how these distinct phenotypes were constructed from a historical perspective and discuss how they are currently coalescing into established genetic etiologies with extensive pleiotropy, emphasizing clinical phenotyping important for diagnosis and for interpreting results from genetic testing. We discuss insights on the pathophysiology of select disorders and describe shared mechanisms that overlap treatment principles in some of these disorders. In the near future, it is likely that a growing number of genes will be described associating movement disorders and epilepsy, in parallel with improved understanding of disease mechanisms leading to more effective treatments.